2019
DOI: 10.1002/oby.22509
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Distribution and Systolic Blood Pressure in 10,000 Adults with Whole‐Body Imaging: UK Biobank and Oxford BioBank

Abstract: Objective This study aimed to quantify the associations of regional fat mass and fat‐free mass with systolic blood pressure. Methods This analysis combined individual participant data from two large‐scale imaging studies: UK Biobank and Oxford BioBank. In both studies, participants were interviewed and measured, and they underwent dual‐energy x‐ray absorptiometry imaging. Linear regression was used to relate systolic blood pressure to anthropometric measures of adiposity (BMI, waist circumference, and waist to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Previous studies have indicated that compared with Europeans, Asians seem to have more abdominal adiposity [16]. Moreover, independent of gender, higher abdominal adiposity, especially abdominal visceral fat, was associated with various metabolic risks, including insulin resistance [23], arterial stiffness [24], higher blood pressure [18] and odds of hypertension. Thus, as showed in our slim medical college students, adiposity indices that capture central fat distribution might be more informative for blood pressure status in young Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that compared with Europeans, Asians seem to have more abdominal adiposity [16]. Moreover, independent of gender, higher abdominal adiposity, especially abdominal visceral fat, was associated with various metabolic risks, including insulin resistance [23], arterial stiffness [24], higher blood pressure [18] and odds of hypertension. Thus, as showed in our slim medical college students, adiposity indices that capture central fat distribution might be more informative for blood pressure status in young Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…BMI is steadily associated with an increased risk of hypertension and type 2 diabetes, although this measure does not account for variation in body fat distribution and abdominal fat mass, which can differ signi icantly across populations and can vary substantially within a narrow range of BMI [16]. Some studies also explored measures accounting for body fat distribution and abdominal fat in different populations [12,17,18]. However, the predictive values of those anthropometric measures were signi icantly different in men and women, in different ethnicities or age groups [6,11,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been investigated about the different mechanisms that could explain the relationship between obesity and hypertension, such as the adipocyte dysfunction, insulin resistance, the sympathetic nervous system and the renin‐angiotensin system dysfunction, or the increased intravascular volume and elevated cardiac output . It has even been suggested that visceral fat is in the origin of excess adiposity underlying the development of adiposity‐related hypertension, according to observational community studies . Lee et al suggested that both quantity and quality of the adipose tissue constitutes a major contributor for the development or prevention of cardiovascular risk factor profiles …”
mentioning
confidence: 99%
“…4 It has even been suggested that visceral fat is in the origin of excess adiposity underlying the development of adiposity-related hypertension, according to observational community studies. 5 Lee et al suggested that both quantity and quality of the adipose tissue constitutes a major contributor for the development or prevention of cardiovascular risk factor profiles. 6 Several studies have explored the relationship of hypertension with obesity in a cross-sectional way.…”
mentioning
confidence: 99%
See 1 more Smart Citation